Dipolar Substitution Impacts Growth and Electronic Properties of Para‐Sexiphenyl Thin Films. Issue 3 (20th December 2019) - Hu, Jiaxin; Aghdassi, Nabi; Bhagat, Shubham; Garmshausen, Yves; Wang, Rongbin; Koch, Norbert; Hecht, Stefan; Duhm, Steffen; Salzmann, Ingo
Abstract: It is shown that fluorination of para ‐sexiphenyl (6P) at the meta ‐ or ortho ‐positions of one terminal phenyl ring, as well as the addition of a terminal cyano‐group has an eminent impact on both growth and electronic properties of thin films. X‐ray diffraction techniques indicate that films of meta ‐substituted 6P ( m ‐2F‐6P) develop a smooth, layered structure showing crystalline order within the layers only. Contrary, both ortho ‐substituted ( o ‐2F‐6P) and cyano‐substituted 6P (CN‐6P) form films of 3D crystalline order. The correlation of structural information with data from ultraviolet photoelectron spectroscopy reveals that m‐2F‐6P and CN‐6P do not show preferentially oriented dipoles in the film, while o ‐2F‐6P grows with collective downward orientation of the dipole moments. The subtle difference in substitution position has a dramatic impact on the thin‐film ionization energy, which increases from 5.40 ( ortho ) to 6.80 eV ( meta ) and reaches even 7.50 eV for CN‐6P. The present study shows that nonsymmetric substitution, which induces molecular dipole moments via intramolecular polar bonds, strongly impacts structure, morphology, and electronic properties of thin films. Thusly modifying common conjugated organic materials represents a valuable tool to establish smooth, crystalline layers with altered energetics at hetero‐interfaces with organic or electrode materials in electronic devices. Abstract : Nonsymmetric dipolar substitution of para ‐sexiphenyl at the meta ‐ or ortho ‐ or para ‐positions of one terminal phenyl ring severely impacts growth and electronic properties of thin films. By changing the substitution position, the thin‐film ionization energies are altered by >1 eV. Thin‐film structures and morphologies range from crystalline and 3D to liquid‐crystalline and 2D which are interesting for electronic applications.